Helminth fauna of chiropterans in Amazonia: biological interactions between parasite and host - de Albuquerque, Ana Cláudia Alexandre [UNESP]; Moraes, Marcela Figueiredo Duarte [UNESP]; Silva, Ana Carolina [UNESP]; Lapera, Ivan Moura [UNESP]; Tebaldi, José Hairton [UNESP]; Lux Hoppe, Estevam G. [UNESP] (Springer Nature, 2016)
Amazonia, the largest Brazilian biome, is one of the most diverse biomes around the world. Considering the Brazilian chiropteran species, 120 out of known 167 species are registered in Pará state, with 10 endemic species. Despite the high diversity of bats in Amazonia, studies on their parasites, especially on helminths, are scarce. Therefore, the present study aims to study the helminth fauna of different bats from the Pará state, Amazon biome, determine the descriptors of infection, and evaluate the host-parasite interactions, as well as evaluate differences in ecological indexes in accordance with the feeding guilds. The study was developed on 67 bats of 21 species captured in several areas of the Pará state. The animals were identified, divided into feeding guilds, and necropsied. The parasites obtained were identified and quantified. A total of 182 parasites were found in 20.89 % of the studied bats, representing nine species, as follows: Anenterotrema eduardocaballeroi, Anenterotrema liliputianum, Ochoterenatrema caballeroi, Tricholeiperia sp., Parahistiostrongylus octacanthus, Litomosoides guiterasi, Litomosoides brasiliensis, Capillariinae gen. sp., and Hymenolepididae gen. sp. Also, the results indicated that there was no impact of parasitism on host body condition and no relationship between sex and parasite intensity. In relation to the feeding guilds, the omnivores showed higher prevalence and mean intensity. Animals from regions closer to the equator tend to have greater richness in parasite species, but the present study revealed low diversity and richness in species. In conclusion, the ecological pattern observed for other animal groups, in which higher parasitic diversity are registered in lower latitudes, is not applicable to chiropterans from the study area.
Keywords: Bats; Biodiversity; Brazil; Feeding guild; Helminth